Konflik Batin dalam lagu “Berita Kepada Kawan“ Karya Ebiet G. Ade Kajian Psikologi - Veran Tika Agustin; Umi Kholidah; Rr Dwi Astuti (PT. ALHAFI BERKAH INDONESIA, 2023)
Conflicts that arise can cause problems both within oneself, between individuals and groups. These problems are very diverse, differences of opinion between a person's heart and mind can cause conflict. The conflict that arises can be in the form of inner conflict. This research aims to determine the inner conflict contained in the song Berita To Friends by Ebiet G. Ade using a literary psychology approach. By analyzing the lyrics of the song